Idiopathic intracranial hypertension presenting as bilateral palpebral venous engorgement - Samantha D. Butterfield; Rona Z. Silkiss (American Journal of Ophthalmology Case Reports)
Purpose: To report the case of a woman in her fifties whose presenting symptom of idiopathic intracranial hypertension was engorgement of the eyelid veins. Observations: Bilateral engorged palpebral veins were visible through the skin. Dilated fundus examination revealed bilateral optic disc edema. Magnetic resonance imaging revealed bilateral posterior globe flattening and empty sella. Magnetic resonance venogram revealed unilateral transverse sinus stenosis. Lumbar puncture revealed elevated opening pressure. All other initial diagnostic tests were negative. Conclusions and importance: Idiopathic intracranial hypertension (IIH) typically presents with headache, vision changes, and weight gain. Palpebral venous engorgement has to the authors’ knowledge not been previously reported as a presenting sign of IIH. Physicians should recognize this finding and its potential association with elevated intracranial pressure.